The linkage between chronotype, social jetlag, and responses to sleep inertia - Fan-Chi Hsiao; Yi-Chen Wang; Ethan Reiter; Changwei W. Wu (Scientific Reports)
Abstract This research explores the interplay between chronotype, sleep inertia (SI), and social jetlag (SJL), examining whether an interaction between chronotype and SJL increases susceptibility to SI in individuals with an evening chronotype, due to their more pronounced SJL. However, a minimal correlation between SJL and SI was observed. The study included 231 participants, all of whom completed a series of questionnaires, including the Morningness-Eveningness Questionnaire (MEQ), the Munich ChronoType Questionnaire (MCTQ), and the Sleep Inertia Questionnaire (SIQ). Our findings indicated that individuals showing greater eveningness exhibited higher levels of SJL. While there was no significant correlation between SJL and SI, and SJL did not mediate the relationship between eveningness and SI, controlling for sex revealed that SJL partially mediated the relationship between chronotype and the Responses to Sleep Inertia, one subscale of SIQ. This suggests that individuals with an evening chronotype are more likely to exhibit behavioral responses indicative of sleep inertia. The findings underscore the complexity of the relationships between chronotype, SJL, and SI, suggesting that SJL does not act as a mediator between chronotype and SI, except for the small mediation effect on behavioral responses. This research provides a foundation for future investigations into the neurophysiological mechanisms underlying SI and how other lifestyle factors influence SI.